Performance Evaluation of a Continuous Downdraft Gasification Reactor Driven by Electric Motors with Manual Mode of Operation - Rachman Setiawan; Hanif Furqon Hidayat; Hafif Dafiqurrohman; Adi Surjosatyo; Radon Dhelika (Journal of Engineering and Technological Sciences, 2022)
Gasification is considered a promising option for harnessing energy potential from agricultural waste, such as rice husks. This paper presents a 10-kW rice husk fixed bed gasifier system. This system is an improved version of a prototype previously developed by our research group. Some of the optimized features added to the gasifier include the use of a circular air intake, an improved gas cleaning system, and electric motors that are regulated by a programmable logic controller. Keeping the gasifier system’s operation stable is critical for producing high-quality synthetic gas (syngas). Therefore, performance evaluation of the presented gasifier system was conducted, and the resulting syngas outputs were analyzed. The evaluation also included an investigation into the performance of the motors, particularly those used for feeding and char removal, which are critical components of the system. The results showed that the improved gasifier system was stable with a proper feedstock. A discussion of the parameters affecting the composition of the synthetic gas is also presented.